Britain and the common market : the effect of entry on the pattern of manufacturing production - Han, S. S.; Liesner, H. H. (Cambridge [Eng.] : University Press, 1971)
This study provides a tentative answers to the question how UK accession to the EEC would affect manufacturing industry in the UK and in the EEC
Includes bibliographical references.
osc 07/11/2018
Loans
Keywords: Manufacturing industries